1997
DOI: 10.1177/0887302x9701500206
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Customer Expectations and Store Policies on Retail Salesperson Service, Satisfaction, and Patronage

Abstract: Apparel retailers are seeking a competitive advantage over other companies and good salesperson service may be a way to create that advantage; however, management may institute policies that are barriers to good salesperson service and thus lose that competitive advantage. In a 2 by 2 laboratory experiment 200 volunteer college women viewed slides of a store's interior, listened to a tape of a salesperson resolving a problem according to store policy, and indicated their satisfaction and patronage intent. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The quality of the interaction between a sales assistant and consumer is determined by the sales assistant's ability to interpret her needs (Hu & Jasper, 2006). Their assistance and advice is more significant when purchasing clothes than other goods (Stanforth & Lennon, 1997), as they can offer knowledge about the merchandise to help the consumer's choice (Solomon & Rabolt, 2004:449) and because clothing shopping is a more deliberate, focussed and high involvement type of shopping than grocery shopping (Lindquist & Kaufman-Scarborough, 2004).…”
Section: The Interaction Between the Female Consumer And Sales Assistmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of the interaction between a sales assistant and consumer is determined by the sales assistant's ability to interpret her needs (Hu & Jasper, 2006). Their assistance and advice is more significant when purchasing clothes than other goods (Stanforth & Lennon, 1997), as they can offer knowledge about the merchandise to help the consumer's choice (Solomon & Rabolt, 2004:449) and because clothing shopping is a more deliberate, focussed and high involvement type of shopping than grocery shopping (Lindquist & Kaufman-Scarborough, 2004).…”
Section: The Interaction Between the Female Consumer And Sales Assistmentioning
confidence: 99%
“…As in the case with all consumer decisions, the clothing consumer finds it important to gather information, tions of the sales assistant can be linked to their perceptions, as expectations are what the consumer thinks is supposed to happen in the store and what they want from their shopping experience (Stanforth & Lennon, 1997). Thus, their perceptions are likely to be influenced by their original expectations when interacting with the sales assistant.…”
Section: The Sales Assistant's Influence On Consumers' Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When expectations are low, customers tend to be satisfied with low levels of service. Previous researchers have investigated the relationships between store type and service expectations (Dotson and Patton, 1992;Lee and Johnson, 1997), customer expectations and retail salesperson service (Stanforth and Lennon, 1997), and service level and retail sales (Morey, 1980). Lee and Johnson (1997) used focus groups to learn more about relationships between store type and customer expectations for apparel customers.…”
Section: Introductionmentioning
confidence: 99%
“…The retail industry connects manufacturing and marketing activities, with customer contact happening at the end of the business value chain (Kotler, 2000). As retailers strive to develop customer-oriented environments, delivering quality and value to the customer through improved customer services has been identified as a way of gaining a potentially competitive advantage (Stanforth & Lennon, 1997). Tohmatsu (2000) suggested that growth of the retail industry is the key index of a nation's economic and social development.…”
Section: Introductionmentioning
confidence: 99%